Aberrant DNA methylation of Tgfb1 in diabetic kidney mesangial cells. Issue 1 (December 2018) - Oba, Shigeyoshi; Ayuzawa, Nobuhiro; Nishimoto, Mitsuhiro; Kawarazaki, Wakako; Ueda, Kohei; Hirohama, Daigoro; Kawakami-Mori, Fumiko; Shimosawa, Tatsuo; Marumo, Takeshi; Fujita, Toshiro
Abstract Epigenetic modulation may underlie the progression of diabetic nephropathy (DN). Involvement of TGFB1 in mesangial fibrosis of DN led us to hypothesize thatTgfb1 DNA demethylation contributes to progression of DN. In primary mesangial cells from diabetic (db/db ) mouse kidneys, demethylation ofTgfb1 DNA and upregulation ofTgfb1 mRNA progressed simultaneously. USF1 binding site inTgfb1 promoter region were demethylated, and binding of USF1 increased, with decreased binding of DNMT1 indb/db compared with control. Given downregulation ofTgfb1 expression by folic acid, antioxidant Tempol reversed DNA demethylation, with increased and decreased recruitment of DNMT1 and USF1 to the promoter, resulting in decreasedTgfb1 expression indb/db mice. Addition of H2 O2 to mesangial cells induced DNA demethylation and upregulatedTgfb1 expression. Finally, Tempol attenuated mesangial fibrosis indb/db mice. We conclude that aberrant DNA methylation ofTgfb1 due to ROS overproduction play a key to mesangial fibrosis during DN progression.